An algorithm based on differential evolution for satellite data transmission scheduling. (2019) - Liang, Qingzhong; Fan, Yuanyuan; Yan, Xuesong; Yan, Ye
Data transmission task scheduling is one of the important problems in satellite communication. It can be considered as a combinatorial optimisation problem among satellite data transmission demand, visible time window and ground station resource, which is a NP-complete problem. In this paper, we propose a satellite data transmission task scheduling algorithm which searches for an optimised solution based on differential evolution algorithm framework. In its progress of evolution, the individual's evaluating procedure is improved by a modified 0/1 knapsack-based method. Extensive experiments are conducted to examine the effectiveness and performance of the proposed scheduling algorithm. Experimental results show that the scheduling results generated from the algorithm satisfy scheduling constraints and are consistent with the expectation.